Athens 2004: the pollution climate and athletic perform - Florida-James, G.; Donaldson, K.; Stone, V. (Journal of Sports Sciences, 2004)
Athens sits in a basin approximately 450 km2 in area, surrounded by mountains and open sea. Anthropogenic emissions in conjunction with the topographical and meteorological conditions can result in high air pollution within the city. The pollutants of concern for athletes competing in Athens 2004 appear to be nitrogen dioxide (NO2), ozone and particulate (PM10) pollution. Exposure to elevated ozone concentrations has been reported to give rise to symptoms that include cough, chest pain, difficulty in breathing, headache, eye irritation and a decrease in forced expiratory volume in one second. All of these effects are likely to impact upon performance, and several studies of cyclists suggest this to be the case. In contrast, the impact of ambient concentrations of NO2 appears to be negligible on normal activities, but at high exercise intensities the impact remains unclear. The use of currently available information and models to predict the effect of ozone and other pollutants on elite athletes is problematical, since such models are based upon significantly lower ventilation rates than those achieved by some elite athletes. In addition, it is already known that the response to ozone can vary somewhat between individuals. Since the individuals who will be competing in Athens are physiologically very different to the participants in most published studies, it is difficult to predict individual responses. There is some evidence to indicate that adaptation to the adverse health and performance effects of ozone can occur, so that performance is partially recovered on re-exposure. The adaptation is not seen in all studies and appears to be dependent on several factors, including the initial sensitivity of the individual to ozone. Antioxidant supplementation has also been shown in some studies to partially ameliorate the adverse effects of ozone by counteracting the oxidative stress mechanism associated with this pollutant. Whether this transfers to performance enhancement per se remains unclear at present. Additional research is required to gain a sound understanding of the effects of a complex mixed air pollution exposure on the pulmonary function and performance of athletes exercising at high work intensities.